Removal Of Cobalt From Sulphate Solutions Using An Electrogenerative Process - Tan , Wan Xin (2011)
An electrogenerative system is applied to removing cobalt from sulphate solutions. In this process, a chemical reaction takes place spontaneously in a divided cell where cobalt is reduced at the cathode and zinc is oxidised at the anode without an external supply of energy. In this work, two types of operating modes (batch reactor and batch-recycle reactor) were investigated.